See it/shoot it : the secret history of the CIA's lethal drone program - Fuller, Christopher J. (Yale University Press, 2017)
An illuminating study tracing the evolution of drone technology and counterterrorism policy from the Reagan to the Obama administrations. This eye-opening study uncovers the history of the most important instrument of U.S. counterterrorism today: the armed drone. It reveals that, contrary to popular belief, the CIA's covert drone program is not a product of 9/11. Rather, it is the result of U.S. counterterrorism practices extending back to an influential group of policy makers in the Reagan administration.